P353Effects of mobilized stem cells on left ventricular function and remodeling in patients with heart failure. (15th July 2014) - Lim, H; Lindarto, D; Zein, U
Abstract: Purpose: The ability of granulocyte colony-stimulating factor (GCSF) to mobilize endothelial progenitor cells (EPCs), as well as to protect cardiomyocytes at risk and to regenerate cardiomyocyte has attracted considerable attention. We hypothesized that G-CSF could improve left ventricular function and remodeling in patients with post-myocardial infarction heart failure. Methods: G-CSF (5.0 mg/kg/day) for 5 days, was administered subcutaneously to 24 patients with post-myocardial infarction heart failure (NYHA functional class II-III). Global left ventricular ejection fraction and left ventricular end-systolic and end-diastolic volumes were assessed by echocardiography. The effects of G-CSF on blood were measured by auto hematology analyzer and semi-auto chemistry analyzer. Flow cytometric analysis of circulating CD34+ hematopoietic progenitor cells was performed. Results: G-CSF increased the white blood cells significantly in the circulation (from 7.7 ±0.3 to 25.2±0.9 x103/ml, p<0.001) and CD34+ cells (from 1.37±0.12 to 23.51±5.37 cells/mL, p<0.001). Indices of platelets, hemoglobin, alanine aminotransferase, lactic dehydrogenase, and uric acid were not changed by treatment. At 1 month post-treatment, there was significant improvement of global left ventricular ejection fraction (43.05 ± 2.94 versus 53.91 ± 2.60 %, p<0.01); and improved left ventricular end-systolic (178.0 ± 8.3 versus 117.3 ± 5.3 ml, p<0.01) and end-diastolic volume (247.0 ± 11.0 versus 180.0± 7.5 ml, p<0, 01). All patients reported mild myalgia which were easily managed with acetaminophen. Conclusions: The results show that G-CSF mobilizes stem cells from bone marrow and improve left ventricular function and remodeling in patients with heart failure. The treatment strategy was safe and tolerable in patients with post-myocardial infarction heart failure.